2019
DOI: 10.3390/molecules24193475
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hepatitis B Virus Activity of Esculetin from Microsorium fortunei In Vitro and In Vivo

Abstract: Coumarins are widely present in a variety of plants and have a variety of pharmacological activities. In this study, we isolated a coumarin compound from Microsorium fortunei (Moore) Ching; the compound was identified as esculetin by hydrogen and carbon spectroscopy. Its anti-hepatitis B virus (HBV) activity was investigated in vitro and in vivo. In the human hepatocellular liver carcinoma 2.2.15 cell line (HepG2.2.15) transfected with HBV, esculetin effecting inhibited the expression of the HBV antigens and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Above all, three compounds (90-92, Figure 33) showed a noteworthy antiviral activity against HCV with EC50 values ranging from 5.1 to 8.4 μM and selective indices (SI = CC50/EC50, which is a measure for the therapeutic window of the compound in an assay system) higher than 20. Huang and co-workers focused their attention on the investigation of the potentiality expressed by esculetin (or 6,7-dihydroxycoumarin) against hepatitis B virus (HBV) [131]. The results suggested that esculetin efficiently inhibits HBV replication both in vitro and in vivo, which provides an opportunity for further development of the compound as antiviral agent.…”
Section: Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, three compounds (90-92, Figure 33) showed a noteworthy antiviral activity against HCV with EC50 values ranging from 5.1 to 8.4 μM and selective indices (SI = CC50/EC50, which is a measure for the therapeutic window of the compound in an assay system) higher than 20. Huang and co-workers focused their attention on the investigation of the potentiality expressed by esculetin (or 6,7-dihydroxycoumarin) against hepatitis B virus (HBV) [131]. The results suggested that esculetin efficiently inhibits HBV replication both in vitro and in vivo, which provides an opportunity for further development of the compound as antiviral agent.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Frequently, inflammatory mediators are the target of anti-inflammatory drugs [134][135][136][137]. Huang and co-workers focused their attention on the investigation of the potentiality expressed by esculetin (or 6,7-dihydroxycoumarin) against hepatitis B virus (HBV) [131]. The results suggested that esculetin efficiently inhibits HBV replication both in vitro and in vivo, which provides an opportunity for further development of the compound as antiviral agent.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Esculetin ( 2 ) from Microsorium fortunei (Moore) Ching. could not only inhibit the expression of the HBV antigens and HBV-DNA but also inhibit the expression of hepatitis B virus X(HBx) protein in a dose-dependent manner [ 20 ]. Chen et al [ 21 ] isolated a series of phenylpropanins from the core material, bark and root of S. asper , all of which had significant anti-HBV activity.…”
Section: The Natural Products Of Anti-hbvmentioning
confidence: 99%
“…Globally, around two billion people show evidence of infection with hepatitis, and about 250-360 million people are chronically infected and at risk for liver disease, according to statistics. Cirrhosis, liver failure, or hepatocellular carcinoma develop in 15-40% of people infected with HBV [1][2][3]. HBV is a DNA virus that encodes surface antigen (HBsAg), core antigen (HBcAg), and pre-core antigen (HBeAg), which are used as diagnostic markers of HBV infection [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhosis, liver failure, or hepatocellular carcinoma develop in 15-40% of people infected with HBV [1][2][3]. HBV is a DNA virus that encodes surface antigen (HBsAg), core antigen (HBcAg), and pre-core antigen (HBeAg), which are used as diagnostic markers of HBV infection [1,2].…”
Section: Introductionmentioning
confidence: 99%